Global trends in depression among patients living with HIV: A bibliometric analysis - Du, Xiaoyu; Zhang, Qian; Hao, Jiaqi; Gong, Xilong; Liu, Jing; Chen, Jia (Frontiers in Psychology, 2023)
Background: Human immunodeficiency virus (HIV) related depression has seriously affected the quality of life and treatment outcomes of patients living with HIV (PLWH), which has become a hot topic in recent years. This study aims to discover the main keywords, predict frontier topics, and give meaningful suggestions for researchers by bibliometric analysis. Methods: Publications between 1999 and 2022 on depression in HIV/AIDS were searched in the Web of Science core collection. Microsoft Excel 2010 and VOSviewer were utilized to key contributors (e.g., authors, journals, institutions, and countries). VOSviewer and CiteSpace were used to analyze the knowledge evolution, collaborative maps, hot topics, and keywords trends in this field. Results: In total, 8,190 publications were included in the final analysis. From 1999-2021, the number of published articles roughly presents a steadily increasing trend. The USA, South Africa, and the UK were three key contributing countries/regions to this field. University Calif San Francisco (USA), University Calif Los Angeles (USA), and Johns Hopkins University (USA) were three key contributing institutions. Safren, Steven A. was the most productive and highest cited author. AIDS Care was the top prolific journal. Antiretroviral therapy and adherence, men has sex with men, mental health, stigma, and Sub-Saharan Africa were the central topics regarding the depression-related research in HIV/AIDS. Conclusion: This bibliometric analysis reported the publication trend, major contributing countries/regions, institutions, authors, journals and mapped the knowledge network of depression-related research on HIV/AIDS. In this field, topics such as “adherence”, “mental health”, “stigma”, “men who have sex with men” and “South Africa” have attracted considerable attention.